Quantitative resistance of rice to blast disease - Sang Won Ahn; Ou, SH (1982)
Eighteen rice cultivars used for differentiating physiologic races of Pyricularia oryzae in the Philippines were repeatedly exposed in the blast nursery, and seven of them artificially inoculated with 40 single-spore isolates. The number of lesions that formed on individual cultivars was negatively correlated with the percentage of resistant reactions of each cultivar to 242 races of P. oryzae in the Philippines, as well as to the 69 races identified during the tests. Cultivars resistant to most races had very few lesions. Accumulation of many vertical or specific resistance genes in a cultivar against many specific races of P. oryzae appears to confer horizontal or general resistance to blast. Comparison of 40 single-spore isolates for pathogenicity indicated that the spore populations of the majority of the isolates were heterogeneous, consisting of many different pathogenic races, very much like that in a blast nursery.